Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/22808000211005384
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic oligopeptide formed enamel-like tissue and dentin tubule occlusion via mineralization for dentin hypersensitivity treatment

Abstract: Objective: Dentin hypersensitivity (DH) is a common oral disease with approximately 41.9% prevalence. Reconstruction of dental hard tissues is the preferred treatment for relieving DH. Here, we applied biomineralization method using oligopeptide simulating cementum protein 1 (CEMP1) to regenerate hard tissues on demineralized dentin. Methods: The self-assembly and biomineralization property of the oligopeptide were detected by scanning electron microscopy (SEM), circular dichroism spectroscopy, and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The roles of templates in the biomimetic mineralization include controlling the shape and size of inorganic structures, chemo-selectivity for inorganic synthesis, inorganic localization, and higher-order assembly. 592 Natural templates such as teeth and bone are often used to mediate the mineralization process to form BMT-like structures, for example, teeth, 554,[594][595][596] demineralized bone, 597 wood, 555 cartilage, 598 and fish scales. 599 Liu et al 554 reported the preparation of continuously structured inorganic materials by crosslinking ionic oligomers.…”
Section: Template-assisted Mineralizationmentioning
confidence: 99%
“…The roles of templates in the biomimetic mineralization include controlling the shape and size of inorganic structures, chemo-selectivity for inorganic synthesis, inorganic localization, and higher-order assembly. 592 Natural templates such as teeth and bone are often used to mediate the mineralization process to form BMT-like structures, for example, teeth, 554,[594][595][596] demineralized bone, 597 wood, 555 cartilage, 598 and fish scales. 599 Liu et al 554 reported the preparation of continuously structured inorganic materials by crosslinking ionic oligomers.…”
Section: Template-assisted Mineralizationmentioning
confidence: 99%
“…If the P 11 -4 complex, formed through the self-assembly of the oligomeric β-sheet-forming peptides, exhibits a similar acicular shape, nanometric size, and crystallinity to natural enamel, it can be considered biomimetic. This biomimetic nature allows the P 11 -4 complex to closely resemble the mineral structure of enamel and potentially support the regeneration and remineralization of dental hard tissues [ 21 ].…”
Section: Self-assembling Peptide P 11 -4 For Ename...mentioning
confidence: 99%